Zoledronic Acid Elicits Proinflammatory Cytokine Profile in Osteolytic Prostate Cancer Cells. (23rd April 2014) - Lin, Yi-Chia; Liao, Po-Cheng; Tsai, Te-Fu; Chou, Kuang-Yu; Chen, Hung-En; Lin, Ji-Fan; Hwang, Thomas I-Sheng
Abstract : Zoledronic acid (ZA), a bisphosphonate used to prevent skeletal fractures in patients with cancers, was demonstrated to induce apoptosis in a number of cancer cells. Our previous study showed that ZA also induces autophagic cell death in metastatic prostate cancer cells. However, the clinical trials using ZA in the treatment of metastatic prostate cancer did not have a longer diseases-free period. Since most of ZA was attracted to the bone after administration, we hypothesized that local prostate cancer cells may evolve prosurvival pathways upon low concentration of ZA treatment. In this study, we investigated the inflammatory effects of ZA on osteolytic PC3 prostate cancer cell, since inflammation was reported to be related to cancer development and survival. Exposure of PC3 cells to various concentrations of ZA resulted in induction of apoptosis and autophagy. The expression of inflammatory biomarkers including interleukin 6 (IL-6), cyclooxygenase-2 (COX-2), and NF- κ B was remarkably upregulated in response to ZA treatment in a dose- and time-dependent manner. The production of IL-6 was elevated upon ZA treatment. The antiapoptotic protein Bcl2 was increased with parallel increased level of IL-6. Our data suggest that treatment with low concentrations of ZA enhances the inflammatory profile and may serve as a prosurvival signaling pathway in PC3 cells.